Unpacking The Role of Design Thinking in Driving Product Innovation : A Systematic Literature Review - Akter, Sharmin (My University, 2025)
This thesis focuses how design thinking (DT) contributes to product innovation, with a particular emphasis on its integration into new product development (NPD) processes. By conducting a systematic literature review (SLR) of 57 peer-reviewed articles published between 2014 and 2024, the study examines how DT is defined, applied, and assessed across different organisational and industry settings. The review is structured around four research questions focusing on the conceptual foundations of DT, implementation challenges, innovation-related outcomes, and emerging areas for future investigation. The findings suggest that DT serves as a dynamic capability that enables organisations to navigate uncertainty, develop user-centred insights, and foster iterative learning. Its core principles – such as empathy, collaboration, and prototyping – support creative problem-solving and cross-functional integration throughout the NPD process. At the same time, the study highlights key obstacles, including cultural resistance, measurement difficulties, and misalignment with established innovation models. Based on the synthesis of insights, the thesis proposes a conceptual framework linking DT practices to innovation performance. This work contributes to a deeper understanding of the strategic role of DT and offers guidance for both researchers and practitioners aiming to apply design-led approaches in product development contexts.
Keywords: Design Thinking (DT); New Product Development (NPD); Product Innovation; Systematic Literature Review (SLR); User-Centric Design; Iterative Prototyping; Innovation Management; Creative Problem-Solving; Dynamic Capabilities; Cross-Functional Collaboration; Empathy in Design; Strategic Innovation; Human-Centered Innovation.